POLICY DIRECTIONS FOR CURRICULUM DEVELOPMENT IN MADRASAH; MANAGERIAL REVIEW - Lahmuddin Lubis; Syamsu Nahar; Luciana Luciana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to analyze the direction of the 2013 curriculum development policy at Madrasah Ibtidaiyah in Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. This research uses a case study qualitative approach, where the researcher conducts interviews, observations, and documentation to obtain the desired data. The data analysis technique follows the Miles and Huberman flow, namely data collection, data reduction, data presentation, and concluding. The study results indicate that the direction of the 2013 curriculum development policy is aimed at strengthening learning that leads to integrative thematic learning, a scientific approach, strengthening character education, providing adequate facilities, developing student skills and talents, and learning assessment based on authentic assessment. This study has implications for the importance of determining policy directions to meet the needs of madrasah citizens to create superior and competitive quality education.